2020
DOI: 10.1002/cyto.b.21877
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HER2 expression in urothelial carcinoma cells as a biomarker for circulating tumor cells

Abstract: BackgroundDetection of circulating tumor cells (CTC) by techniques based on epithelial cell adhesion molecule (EpCAM) is suboptimal in urothelial carcinoma (UC). As HER2 is thought to be broadly expressed in UC, we explored its utility for CTC detection.MethodsHER2 and EpCAM expression was analyzed in 18 UC cell lines (UCCs) by qRT‐PCR, western blot and fluorescence‐activated cell scanning (FACS) and compared to the strongly HER2‐expressing breast cancer cell line SKBR3 and other controls. HER2 expression in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Ideally, these tracers visualise unique characteristics of UCC which distinguishes the tumour from adjacent normal tissue. In case of uPAR and EpCAM, these membrane receptors have complementary expression patterns during the complex multistep process of switching from a sessile to an invasive cancer cell [24,25]. In addition to uPAR targeting, we show our recently introduced EpCAM-targeting tracer, which is currently being evaluated on patients with gastrointestinal cancer, could also be used for UCC (NL7363) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, these tracers visualise unique characteristics of UCC which distinguishes the tumour from adjacent normal tissue. In case of uPAR and EpCAM, these membrane receptors have complementary expression patterns during the complex multistep process of switching from a sessile to an invasive cancer cell [24,25]. In addition to uPAR targeting, we show our recently introduced EpCAM-targeting tracer, which is currently being evaluated on patients with gastrointestinal cancer, could also be used for UCC (NL7363) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Also, no statistically significant relation could be detected between HER2 expression and grading of UD cases. Similarly, in a study by Mohamad et al (2014) and Nini et al (2020) no statistically significant relation was reported regarding age and sex with respect to HER2 overexpression in their studied cases.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, the interaction of BF 2 -possessing compounds with HER2 receptors can be involved in the cytotoxic activity of these compounds [ 32 ]. Based on the literature data, both cell lines used in our studies, 5637 and SCaBER, expressed the HER2 receptor [ 39 ]. The similar IC 50 values calculated for our BF 2 complexes toward 5637 and SCaBER cells could potentially result from this interaction.…”
Section: Resultsmentioning
confidence: 99%